Adaptiveness of emotion regulation flexibility according to long-term implications - Prüßner, Luise; Ortner, Catherine N. M. (Journal of affective disorders, 2025)
Background - The ability to consider the long-term implications of emotional events is integral to mental health and adaptive psychological functioning. However, it remains unclear whether flexibly synchronizing emotion regulation strategies to the long-term implications of emotional events is associated with adaptive outcomes. - Methods - This ecological momentary assessment study examined how emotion regulation flexibility concerning contextual long-term implications is linked to daily emotional experiences and mental health outcomes. Ninety-eight participants provided 1705 real-time assessments of their perceived long-term implications of ongoing emotional events and reported their use of cognitive change (i.e., reappraisal, benefit-finding, perspective-taking) and attentional deployment strategies (i.e., distraction, refocusing, cognitive avoidance). The adaptiveness of adjusting these strategies based on contextual long-term implications was examined using momentary emotional experiences and measures of psychopathology and well-being as outcomes. - Results - Consistent with models of emotion regulation flexibility, participants who aligned their use of cognitive change and attentional deployment strategies with the perceived long-term significance of events reported more positive daily emotional experiences and lower levels of psychopathology. - Limitations - Future work should use experimental and longitudinal designs to establish causal pathways. - Conclusions - These findings underscore the importance of accounting for situational long-term implications when evaluating the adaptiveness of regulatory strategies, thereby adding to the growing body of evidence supporting the contextual nature of emotion regulation.